In search of factors contributing to the development of small satellite communes, or how distance from the city centre impacts the development of the communes of Iwanowice and Zielonki: An interview with the mayor of the commune of Iwanowice, Mr Zbigniew Grzyb. An interview with the mayor of the commune of Zielonka, Mr Arnold Kuźniarski - Rosa, Anna (Journal of Public Governance, 2018)
.